Pengurusan kredit mikro di kalangan wanita - Zaimah Ramli, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
The effort of Amanah Ikhtiar Malaysia (AIM) in providing micro-credit to the poor women will give opportunity for them to start their economics activities that can upgrade their family quality of life. Hence, this article focus on how the Sahabat (AIM member‟s) that had received the micro-credit facilities manage their credit in order to achieve what that had planned. The result shows that most of the Sahabat used their facilities to finance their economic activities that they undertaken. Other than that, some portion of the credits facilities are also being used to renovate their home and pay for their children education fees. What need to be given serious attention is most of them put less important on matters pertaining their financial management. Sahabat are also not really concern about their cash flow record on their economic activities. Most of them will only make sure that they will be able to pay their credit on the weekly payment as scheduled. They consider that by paying the credit as schedule is the benchmark of their successfulness as being the Sahabat of AIM. Nevertheless, the micro-credit scheme is very helpful and beneficial to the Sahabat, especially to the women